Multiscale skin imaging in vivo using optical coherence tomography - Yu, Xiaojun (2020)
Optical coherence tomography (OCT) is a noninvasive high-resolution diagnostic imaging modality that plays an increasingly important role in dermatology. Diagnosis of skin diseases using OCT requires both cellular-level high resolution and large area skin coverage. In practice, however, there exists a trade-off between the achievable spatial resolutions and the transverse scanning range. In this study, we report a Micro-OCT (μOCT) system that is capable of providing three-dimensional images of the skin at multiple spatial scales with both cellular-level resolution (1-2 μm) mode and large area (∼ mm2) scanning mode. Specifically, in the cellular-level scanning mode, we achieve a transverse resolution of ∼1.5 μm and an axial resolution of 1.7 μm (n = 1.38) which enables the visualization of cellular-level skin microstructures. While in the large-area scanning mode, the system is capable of covering an en face imaging area reaching up to with a lateral resolution of ∼5.5 μm at a scanning speed of 60 K Alines/s. We experimentally verify the imaging capabilities of such a multiscale μOCT system including in vivo visualization of epidermal cells in the cellular-level scanning mode as well as the internal fingerprints and sweat gland ducts in the large area scanning mode. Micro-anatomical imaging at multiple spatial scales could provide comprehensive information of the skin that is valuable to disease diagnosis.